2013
DOI: 10.1128/aac.02619-12
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization and In Vitro Antifungal Susceptibility Profile of Schizophyllum commune, an Emerging Basidiomycete in Bronchopulmonary Mycoses

Abstract: dSchizophyllum commune (n ‫؍‬ 30) showed lowest geometric mean MICs of isavuconazole (0.19 g/ml), itraconazole (0.2 g/ml), voriconazole (0.24 g/ml), and amphotericin B (0.29 g/ml) and high geometric mean MICs of fluconazole (19.39 g/ml) and flucytosine (17.28 g/ml). Five cases (of 8) of allergic bronchopulmonary mycosis that were treated with itraconazole had no recrudescence after 6 to 24 months of follow-up. One case each of invasive pulmonary mycosis and fungal ball were treated successfully with voriconazo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 27 publications
4
29
1
Order By: Relevance
“…In agreement with the findings of other studies (30,31), AMB showed the highest in vitro potency against most Schizophyllum isolates tested. The strains of S. commune tested here had low MICs for PSC and VRC (0.20 g/ml for both), similar to previous reports (30,31). For S. radiatum, our results revealed high degrees of variability in the activities of the agents tested among strains, especially for the azoles and for TBF (Table 2).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…In agreement with the findings of other studies (30,31), AMB showed the highest in vitro potency against most Schizophyllum isolates tested. The strains of S. commune tested here had low MICs for PSC and VRC (0.20 g/ml for both), similar to previous reports (30,31). For S. radiatum, our results revealed high degrees of variability in the activities of the agents tested among strains, especially for the azoles and for TBF (Table 2).…”
Section: Discussionsupporting
confidence: 82%
“…In fact, a correlation between in vitro data and clinical efficacy has not been well established (54). In agreement with the findings of other studies (30,31), AMB showed the highest in vitro potency against most Schizophyllum isolates tested. The strains of S. commune tested here had low MICs for PSC and VRC (0.20 g/ml for both), similar to previous reports (30,31).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…In vitro susceptibility data for 40 NSM isolates tested are presented in Table 3. With the exception of POS and CAS findings, the susceptibility profiles of S. commune isolates have been presented previously (25). All of the tested species of basidiomycetes were susceptible to AMB and resistant to CAS, fluconazole, and flucytosine.…”
Section: Characteristics Of Cultured Isolatesmentioning
confidence: 99%